Plastic Filtration and Decomposition According to Ricochet Filtering Mechanism Using Ideonella sakaiensis - Sankrityayan, Prakhar; Biswas, Sumit (Frontiers in Marine Science, 2022)
According to a United Nations report (2016), at least 800 species were being affected worldwide due to marine debris, of which 80% were plastics. Microplastics are small pieces of plastic measuring less than five mm. The majority of these tiny plastic particles are created by disintegration of larger plastic items such as polystyrene bags, etc. One significant cause for the mortality of these fishes is the intake of such plastics. Tiny, fancy fishes are affected due to the choking of their gills with microplastics since they are natural filter feeders. Microplastics also attract toxins (such as DDT) from the surrounding marine environment, making them even more potentially hazardous to any animal eating them, including those higher trophic level in the food chain. This study aims to develop a small-scale solution for the problem of oceanic plastic pollution, which could later be scaled up by increasing the size and number of units as required. This system has been inspired by the filter-feeding mechanism of manta rays and uses a bacteria named Ideonella sakaiensis for the decomposition of plastic that has been filtered. The whole system is supposed to be a floating system where the filtration units would be submerged under water, and a unidirectional flow of water could be created by placing a fan at the end of these filtration units. Each filtration unit has multiple layers of sieving, vortexing, and cross-flow filtration with a batch of I. sakaiensis at the end, which would aid in decomposing the plastic